In Vitro Activity of a New Ophthalmic Spray Containing Biosecur® Citrus Extract (Oftasecur®) Against Candida auris and Candida albicans and Preformed Biofilm on Contact Lenses - Antonio Pinna; Matthew Gavino Donadu; Stefano Dore; Rita Serra; Matteo Sacchi; Giacomo Boscia; Aliz Bozó; Renátó Kovács (Vision)
We investigated the in vitro antifungal activity of a new commercial ocular spray containing Biosecur® citrus extract (Oftasecur®) against Candida auris and C. albicans and assessed its activity against preformed Candida biofilm on contact lenses and plastic lens cases. The C. auris isolate 12 (NCPF 8973) and the SC5314 C. albicans wild-type reference strain were used. Oftasecur®’s effect on C. auris and C. albicans planktonic cells (1 × 106 cells/mL) was tested in RPMI-1640 medium. The concentrations tested were 0.39%, 1.56%, 6.25%, 12.5%, and 25%. The living planktonic cell number was obtained using time-kill experiments. Antifungal activity against preformed C. auris and C. albicans biofilm on etafilcon A and senofilcon A contact lenses and plastic lens cases was also tested. A significant decrease was found in the living cell number of C. albicans after 8–48 h in the presence of Oftasecur® concentrations ranging from 6.25% to 25% (p < 0.01–0.001). In the C. auris experiments, the cell number was significantly decreased after 8 h incubation in 25% Oftasecur® (p < 0.05–0.001). Similarly, 12.5% Oftasecur® was effective against preformed C. auris and C. albicans biofilm on contact lenses and plastic lens cases. The results suggest that the in vitro antifungal activity of Oftasecur® against C. albicans and C. auris planktonic cells and preformed fungal biofilm on contact lenses and plastic cases is dependent on the concentrations used. Further research is warranted to establish whether Oftasecur® may play a role in the prevention of contact lens-related Candida keratitis and other ocular-surface Candida infections.